2012
DOI: 10.1111/j.1460-9592.2012.03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for surgery related to craniosynostosis: a review. Part 2

Abstract: The management of children with craniosynostosis is multidisciplinary and has evolved significantly over the past five decades. The treatment is primarily surgical. The anesthetic challenges continue to be the management of massive blood transfusion and prolonged anesthesia in small children, often further complicated by syndrome-specific issues. This two-part review aims to provide an overview of the anesthetic considerations for these children. The first part described the syndromes associated with craniosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
2
35
0
2
Order By: Relevance
“…Additionally, some metabolic syndromes may be encountered after craniosynostosis surgery [23]. Some studies recommend a minimum of 24 h of follow-up of patients postoperatively [8,24]. We did not encounter serious complications in the postoperative period.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Additionally, some metabolic syndromes may be encountered after craniosynostosis surgery [23]. Some studies recommend a minimum of 24 h of follow-up of patients postoperatively [8,24]. We did not encounter serious complications in the postoperative period.…”
Section: Discussionmentioning
confidence: 85%
“…Anesthetic management during corrective surgery of craniosynostosis is very challenging. Serious problems can be encountered, most of which are related to blood loss during the operation and hemodynamic instability, where blood loss generally exceeds 40 ml/kg [8,12]. van Uitert et al [5] found an average of 55.2 ± 39.8 ml/kg blood loss in their study of 44 craniosynostosis patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations